2017
DOI: 10.18632/oncotarget.21163
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, ultra low coverage copy number profiling of cell-free DNA as a precision oncology screening strategy

Abstract: Current cell-free DNA (cfDNA) next generation sequencing (NGS) precision oncology workflows are typically limited to targeted and/or disease-specific applications. In advanced cancer, disease burden and cfDNA tumor content are often elevated, yielding unique precision oncology opportunities. We sought to demonstrate the utility of a pan-cancer, rapid, inexpensive, whole genome NGS of cfDNA approach (PRINCe) as a precision oncology screening strategy via ultra-low coverage (~0.01x) tumor content determination t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 76 publications
(80 reference statements)
2
51
0
Order By: Relevance
“…13 Additional studies have used array-CGH and deep AR gene sequencing 10,16 or targeted sequencing across 72 clinically relevant genes. 35 Our plasma-Seq was the first description of low-coverage sequencing of plasma DNA 18 and as it is being adapted by other groups, 40,41 it is currently evolving into a widely used tool for genome-wide SCNA analysis. With the addition of targeted sequencing at high coverage of relevant genes, a wealth of information for improving the management of patients can be generated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Additional studies have used array-CGH and deep AR gene sequencing 10,16 or targeted sequencing across 72 clinically relevant genes. 35 Our plasma-Seq was the first description of low-coverage sequencing of plasma DNA 18 and as it is being adapted by other groups, 40,41 it is currently evolving into a widely used tool for genome-wide SCNA analysis. With the addition of targeted sequencing at high coverage of relevant genes, a wealth of information for improving the management of patients can be generated.…”
Section: Discussionmentioning
confidence: 99%
“…This enabled us to show the presence of this deletion at the subclonal level in the previous samples, as we identified very low numbers of respective fusion fragments (35153-89: 41; 35153-90: 9; 35153-91: 40). Some of the emerging somatic alterations, such as loss of PTEN or RB1 and the novel gain of 20q13 which harbors the AURKA gene, have been reported as frequent changes in neuroendocrine prostate cancer (NEPC) [37][38][39][40][41] and represent a potential therapeutic target. 42 Such clonal pattern changes during the transition from prostate adenocarcinoma to a neuroendocrine tumor have previously been described by our group and others.…”
Section: Clinical Significance Of Longitudinal Tumor Genome Monitoringmentioning
confidence: 99%
“…To determine the tumor content (TC) in cfDNA, we used a wellestablished method PRINCe (pan-cancer, rapid, inexpensive, wholegenome NGS of cfDNA approach) for tumor content determination and to identify focal CNAs in cfDNA from mCRPC patients' samples via low coverage (~0.01x) through genome-wide CNAs analysis, where the least-squares based distance metric (LSS) was performed on whole-genome copy number data, and guide the tumor content approximation with low tumor content samples (LSS < 0.1), where estimated tumor contents greater than 8.75% by LSS analysis were considered as high tumor content as previously described by Daniel H. Hovelson et al, 2017. 34 Focal CNAs were measured as CNAs 1.5 to 20 Mb long with the log2CNRatio cutoffs for genomic gain and loss analyzed in lpWGS were ≄ 0.50 and ≀−0.50, respectively.…”
Section: Low-pass Whole Genome Sequencing Tumor Content and Copy Nmentioning
confidence: 99%
“…19 The tumor content was determined in cfDNA from wholegenome sequencing data using the PRINCe method according to previously described methods. 34 After determining the tumor content in cfDNA, we compared the distribution of CellSearch CTCs in 68 baseline mCRPC men from PROPHECY study with low tumor content (lowTC) (n = 40) and high tumor content (highTC) (n = 28). We found that CellSearch CTC counts were significantly higher in highTC cfDNA (P-value = .0001) in comparison to lowTC cfDNA samples ( Figure S2C).…”
Section: Patients With Mcrpc Demonstrate Heterogeneous Cfdna Concenmentioning
confidence: 99%
“…One of the advantages in this strategy is that the confounding from background noise is less pronounced when rearrangements are targeted instead of SNVs [12]. WGS can also be used for direct sequencing of plasma DNA to generate a copy number profile of the tumor, if the ctDNA fraction in plasma is >5-10% [51], and may identify treatment-targetable focal amplifications [52]. Furthermore, as the analysis requires no prior knowledge of the genetic characteristics of the tumor, it can be applied directly without the use of a tumor tissue biopsy.…”
Section: Approaches For Detection Of Ctdnamentioning
confidence: 99%